Bantuan Hukum Pro Bono Sebagai Pilar Strategis Dalam Penegakan Hak Asasi Manusia Di Indonesia - Muflikh, Alna Aulin Miftakhul; Hert, Daiva Ebiandre; Purba, Calvin Axel; Silalahi, Bob Ben Saloman (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Pro bono legal aid plays a crucial role in ensuring access to justice for groups of people who are economically unable to afford commercial legal services. In the context of the rule of law and the protection of human rights, the existence of pro bono legal aid not only reflects the social concern of the advocate profession, but is also an important element in the implementation of the principle of equality before the law. This article examines the contribution of pro bono legal aid to the enforcement of human rights in Indonesia through a juridical-normative approach with qualitative analysis of laws and regulations, professional codes of ethics, and practices in the field. The findings show that despite the normative obligation for advocates to provide pro bono services, there are still various structural barriers, including the lack of institutional support, low appreciation of pro bono services, and operational constraints in the field. Therefore, it is necessary to strengthen policies, inter-institutional synergies, and internalize social justice values in legal aid practices to ensure that pro bono is not only a formal obligation, but also the ethos of advocates' struggle in realizing substantive justice for all citizens.